CONSUMER TRUST AND COUNTRY OF ORIGIN (Chinese Product Case on Indonesian Market) - Hotniar Siringoringo; Margianti E.S.; Anacostia Kowanda; Trini Saptariani (Universitas Gunadarma, 2012)
Study on Indonesian consumer trust towards Chinese products is rarely found. Low trust towards Chinese as producer as well as towards Chinese products perhaps is admitted by almost all consumers. However up to this time period this hasn’t become researcher’s interest. The objective of the study is thus to identify consumer trust towards Chinese products. Electronics product particularly was chosen as research object based on its penetration on Indonesian markets. For this purpose questionnaire was used as research instrument. It was distributed to more than 300 respondents. Results show that consumer trust towards Chinese products is measured using four indicators, such as faith and believe in Chinese products, Chinese high technology and long lasting live. Country of origin has five valid indicators which are Chinese innovativeness on electronics products, Chinese high technology, Chinese creativity in design, good quality in manufacture, and China as prestigious country. The highest contributor in building country of origin is its high technology. On trust factor, the highest contributor is customer believe in Chinese electronics products. It also shows that country of origin influence customer trust significantly. Key Words : consumer trust, country of origin, Chinese products, Indonesian mar- ket.